Peran Aparat Penegak Hukum Dalam Menangani Tindakan Pihak Polres Kota Gorontalo Terhadap Penggunaan Handphone Saat Berkendara Pada Ojek Online - Mateka, Siti Nurlam; Kasim, Ramdhan; Bilondatu, Agustina A. (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
This study aims to find out about how the application of Law Number 22 of 2009 concerning traffic and road transportation to the use of mobile phones while driving on online motorcycle taxis, and how the Gorontalo City Police take action against the use of mobile phones while driving on online motorcycle taxis. This research uses normative-empirical research where this research examines the implementation or implementation of positive legal provisions (legislation) and written documents in action (factual) in every particular legal event that occurs in society. The review aims to ascertain whether the application of law in in concreto legal events is in accordance or not with the provisions of the existing laws and regulations. Legal research has several approaches that can be used, but in this study the researcher uses a statute approach where this approach is carried out by examining all laws and regulations related to the legal issue being studied. The results of the study show that traffic itself is an important element in any program to regulate road transportation so that it can operate efficiently and to minimize accident rates. Transportation is a primary need in human life, blood for the economy which is needed most fundamentally at this time. Using a cell phone while driving can interfere with the driver's concentration, because his concentration and attention are divided between the road and the cellphone he is using. The use of mobile phones while driving has been regulated in Law Number 22 of 2009 concerning Road Traffic and Transportation in Article 106 Paragraph (1) which stipulates that the driver must be fully concentrated when driving. Driving a vehicle properly and with full concentration means not driving a vehicle when you are sick, tired or under the influence of alcoholic beverages. Regarding the prohibition on the use of mobile phones while driving, this is not specifically regulated in Law Number 22 of 2009, but drivers who use mobile phones while driving can be subject to Article 106 paragraph 1 as mentioned above. The rise of online transportation services that rely heavily on GPS installed on the mobile phone itself, so legal certainty is needed for clarity on the use of GPS while driving. Sanctions for using mobile phones while driving have also been regulated in the Road Traffic and Transportation Act in Article 283 with the threat of imprisonment for a maximum of 3 (three) months or a fine of up to Rp. 750,000.00 (seven hundred fifty thousand rupiah).